MULTIFUNCTIONALITY OF THE «WAR» CONCEPT IN THE ARTISTIC SPACIOUSNESS OF THE LEOPOLD BUCHKOVSKY’S NOVEL «BLACK STREAM» - Tovt, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Developing the problem of antimilitarity in the artistic space of Ukrainian national writing, I repeatedly turn to the aesthetic experience of Middle-Neighborly literatures. Therefore, the purpose of this article is to analyze prose in Polish belles-lettres, particularly in Leopold Buchkovsky’s landmark novel "Black Stream." His work attracks the modern reader from different positions. That’s at least because of the fact that such eternal questions as the existence of life and death, tragedy and morality, honor and betrayal, courage and fearfulness, are being raised. In reality, all that war inflicts upon any populace, regardless of the era. The multidimensionality of this concept is obvious and associatively close to our national present, especially during the current Ukrainian confrontation against the Russian invaders. Therefore, the methods of study, that correspond to the declared topic: analytical, hermeneutical, comparative-typological and cultural-historical, are used in the research. As a consequence, clarification of the problem is proved that the concept of "war" in the prose of the Polish author Leopold Buchkovsky is multifunctional. It permeates the entire ideological and aesthetic fabric of the novel "Black Stream" at both content and formative levels. This determines the novelty of the study. At the same time, such an approach in the analysis of a prose work by a Polish writer provides the necessary practical significance of the study: it can be used by both literary scholars (Polish and Ukrainian) and modern teachers in the development and submission of antimilitary literature issues in educational institutions.